Um, at x=A
L(A) = cosA
L'(A) = -sinA
L''(A) = -cosA
Now to match the value of the function and also the 1st and 2nd derivatives.
let:
f(A) = a(e^A)+bA+c = L(A) = cosA
f'(A) = a(e^A) + b = L'(A) = -sinA
f'(A) = a(e^A) = -cosA
=> a = -cosA*e^-A
b = -sinA - a(e^A) = -sinA + cosA
c = cosA - a(e^A) - bA = cosA + cosA -A(-sinA + cosA) = 2cosA - A(cosA - sinA)
so f(x) = -cosA*e^-A*e^x + (cosA - sinA)x + 2cosA - A(cosA - sinA)
= - cosA*e^(x-A) + (cosA - sinA)x - A(sinA - cosA)
as an approximations of L(x) = cosx, at x=A, in the form a(e^x) + bx + c.
Though that's not a linear approximation, as the title suggests.